2021
DOI: 10.2147/ijgm.s305491
|View full text |Cite
|
Sign up to set email alerts
|

Retarding Progression of Chronic Kidney Disease in Autosomal Dominant Polycystic Kidney Disease with Metformin and Other Therapies: An Update of New Insights

Abstract: Autosomal dominant polycystic kidney disease (ADPKD) is the most frequent single-gene disorder leading to renal failure. Current therapies are aimed to treat renal and extrarenal complications of ADPKD, but improved knowledge of the pathophysiological mechanisms leading to the generation and growth of cysts has permitted the identification of new drug candidates for clinical trials. Among these, in this review, we will examine above all the role of metformin, hypothesized to be able to activate the AMP-activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 80 publications
0
2
0
1
Order By: Relevance
“…Metformin is a novel and attractive therapeutic candidate for ADPKD. Metformin inhibits the mTOR and CFTR pathways and activates AMPK, which has been associated with reduced renal cyst growth in an ADPKD mouse model ( Takiar et al, 2011 ; Carullo et al, 2021 ; Pastor-Soler et al, 2022 ). In the present analysis, metformin also showed a favorable trend, but it was not significant, possibly because of a small sample size.…”
Section: Discussionmentioning
confidence: 99%
“…Metformin is a novel and attractive therapeutic candidate for ADPKD. Metformin inhibits the mTOR and CFTR pathways and activates AMPK, which has been associated with reduced renal cyst growth in an ADPKD mouse model ( Takiar et al, 2011 ; Carullo et al, 2021 ; Pastor-Soler et al, 2022 ). In the present analysis, metformin also showed a favorable trend, but it was not significant, possibly because of a small sample size.…”
Section: Discussionmentioning
confidence: 99%
“…Another drug that can enhance autophagic flux is metformin. This agent is mainly used to treat type 2 diabetes mellitus, but it can also activate AMPK, the master inducer of autophagy [100,101]. Experimental studies showed that metformin may prevent the progression of cysts and protect kidney function [102].…”
Section: Autophagy Regulators In Adpkdmentioning
confidence: 99%
“…Su indicación debe acompañarse del conjunto de medidas no específicas dirigidas a enlentecer la progresión de la ERC (20) . Junto con la búsqueda de estrategias para minimizar los efectos adversos del tratamiento con tolvaptán (21) , un conjunto de nuevos fármacos se encuentran en desarrollo y evaluación con el fin de constituirse en tratamientos específicos dirigidos a enlentecer la progresión de la ERC en pacientes con PQRAD (22)(23)(24)(25)(26)(27) .…”
Section: Conclusiones Y Perspectivasunclassified